2016
DOI: 10.1080/00224545.2016.1263595
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulation and social pressure reduce prejudiced responding and increase the motivation to be non-prejudiced

Abstract: Self-regulation constrains the expression of prejudice, but when self-regulation falters, the immediate environment can act as an external source of prejudice regulation. This hypothesis derives from work demonstrating that external controls and internal self-regulation can prompt goal pursuit in the absence of self-imposed controls. Across four studies, we found support for this complementary model of prejudice regulation. In Study 1, self-regulatory fatigue resulted in less motivation to be non-prejudiced, c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Many studies showed that personal moral judgment is influenced not only by subjective factors such as personal experience, cognitive level, and psychological characteristics, but also by public opinions and attitudes. Buzinski and Kitchens (2017) proposed that public opinions could change individuals' attitudes to a given event by affecting their psychological state and moral judgment. In pro-social scenarios, bystanders are more likely to defend victims.…”
Section: Collective Sentiment On Social Media and Cyber-bystanders' R...mentioning
confidence: 99%
“…Many studies showed that personal moral judgment is influenced not only by subjective factors such as personal experience, cognitive level, and psychological characteristics, but also by public opinions and attitudes. Buzinski and Kitchens (2017) proposed that public opinions could change individuals' attitudes to a given event by affecting their psychological state and moral judgment. In pro-social scenarios, bystanders are more likely to defend victims.…”
Section: Collective Sentiment On Social Media and Cyber-bystanders' R...mentioning
confidence: 99%
“…In so doing people might have explicitly changed their answers to not come across as conforming to stereotypes or the implicit reactions of participants is so small that the current study was not able to find them. Correcting one's own behaviour/answers is a common reaction in socially sensitive domains such as prejudice (Buzinski and Kitchens 2017;Dovidio et al 2002). Future research could therefore benefit from developing measures or utilizing existing measures that capture the implicit processes, e.g., the Implicit Association Test by Greenwald (Craig and Richeson 2014;Fazio and Olson 2003;Redford et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Some scientists point out that self-regulation ensures formation of sustainable forms of behavior and response. Lack of internal control can be compensated by external influences and motivation, thus ensuring achievement of the goal (Buzinski & Kitchens, 2017).…”
Section: The Content and The Concept Of Psychological Self-regulation...mentioning
confidence: 99%
“…It follows that the individual is self-actualizing and selfdeveloping with the help of internal psychological resources. At that, selfsufficiency is ensured by the level of consistency of personal potential with the level of claims (Buzinski & Kitchens, 2017).…”
Section: The Essence Of Self-sufficiency Of An Individual In the Stru...mentioning
confidence: 99%